Evaluation of Performance of Women Self Help Groups - Devi, E. Jenita; Anand, Sarita (Indian Journal of Extension Education, 2012)
Women are critical and vital constituent of Indian economy both at national and household level. They make up one-third  of the national labour force. But poverty and unemployment are the twin evils faced by women in our society. Universally,  Self Help Groups (SHGs) have been accepted as a means for poverty alleviation and empowerment of poor and marginal  rural women. Therefore, SHGs are promoted and implemented everywhere under different schemes. But a meagre work  has been done on evaluation of performances of these SHGs on area, trade or regional specifics with varied  socioeconomic and traditions, particularly in the context of the state of Manipur. This paper is an earnest attempt by the  researchers to fill up this gap.
Keywords: Self help groups (SHGs); performances; household